Recent Sediments: The Front Line of Environmental Protection - Fyfe, W. (Geoscience Canada, 1982)
Abstract Man has become the greatest agentmodifying surface environmentalsystems. Our knowledge of the balancebetween these systems is inadequate andat present we cannot predict theconsequences of major perturbations.Perhaps the greatest problem facing ourscience is the understanding of climatebut if such knowledge is to be obtained,the record must be extracted from rocksnear the surface of the earth.